Indigenous entomopathogenic nematodes from China for the biological control of Spodoptera litura (Lepidoptera: Noctuidae): a multistage evaluation - Jiale Xi; Tianyu Wu; Lei Liu; Yinuo Xu; Xiwen Lin; Xianqin Wei; Xiangde Yang; Weibin Ruan (Crop Protection, 2027)

Primary biliary cirrhosis and rheumatoid arthritis: a comprehensive study combining genetics and transcriptomics - Mingyi Yang; Honghao Ren; Xiaodong Ren; Pengfei Wen; Jiale Xie; Xianjie Wan; Ke Xu; Lin Liu; Weikun Hou; Zhi Yang; Peng Xu (Mammalian Genome, 2026)

Durable and efficient 2D/3D perovskite bulk heterojunction solar cells via BA2MAPb2I7 single crystal addition - Zihong Cai; Xin Chen; Zixing Guo; Yafei Wang; Tianqi Niu; Junyu Lin; Shihai Ye; Qianqiu Guan; Jiazhen Xu; Jiale Huang; Tao Zou; Zuoshan Zhang; et al. (Chemical Engineering Journal, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Graphdiyne-based sensing interfaces for bioactive molecules: Structural features, structure–activity relationships, and practical challenges - Yingtong Dong; Linbo Li; Junru Li; Jiayao Wulan; Jiale Wei; Daixin Ye; Yuqing Lin (Chemical Engineering Journal, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Intelligent aeration technologies in grain storage: A comprehensive review of multi-physics modeling and AI-driven control - Xiaoyu Zhang; Jiale Guo; Yanhong Liu; Yuanyi Luo; Shuanglin Wang; Deqing Wang; Jie Lin; Kun Hu; Haoyu Wen; Yining Wu; Xiaoping Yan (Journal of Stored Products Research, 2026)

Electrochemical strategies for efficient PFAS removal from water: Mechanisms, performance, and sustainability perspectives - Kaini Peng; Jiale Lin; Mei Chen; Junjian Zheng; Yang Li; Liang Tang (Journal of Hazardous Materials, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Enzyme-immobilized metal-organic framework biosensor for target-triggered sensitive fluorescence detection of diazinon residue and accumulation in rice - Tingting Cai; Yiran Li; Jiale Song; Lin Zhou; Zitong Wang; Binshuo Guo; Jie Gao; Guanghao Chen; Jintong Liu; Hong Yang (Journal of Cleaner Production, 2026)

Design and optimization of an autothermal solid oxide electrolysis cell reactor for efficient and economical solar-driven carbon dioxide reduction - Zihan Lin; Junjie Hou; Haoran Li; Qi Xia; Jiale Long; Zhouxin Pan; Muhammad Sajid Khan; Chen Chen (Journal of Cleaner Production, 2026)

WITHDRAWN: Corrigendum to "H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing" [Chem. Eng. J. 469 (2023) 143398] - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2026)

Aptamer-driven tetrahedral framework nucleic acids for targeted resveratrol delivery in ulcerative colitis therapy - Botao Liu; Siyi Yang; Jiale Liang; Lan Yao; Bo Huang; Yu Chen; Yun Wang; Yunfeng Lin (Chemical Engineering Journal, 2026)

A label-free fluorescent/electrochemical dual-mode zinc complex biosensor for highly selective and sensitive detection of tetracycline - Zhi-Lin Mu; Zeyu Zhu; Jiale Cheng; Xingyu Zhan; Chen He; Zhongyan Chen; Hong-Ping Xiao; Jing-Yuan Ge (Analytica Chimica Acta, 2026)

Moderate net-chasing enhances stress resilience in freshwater prawns Macrobrachium rosenbergii: evidence from behavioral and physiological recovery - Jiangtao Li; Jiale Zhou; Licheng Zeng; Yingtong Ou; Zhongjie You; Zheng Xiao; Jianjun Guo; Li Lin; Xiaojing Lv (Aquaculture, 2026)

Experimental and theoretical insights into oxytetracycline and sulfamethoxazole adsorption onto four biomass-derived nanosized activated carbons in aquatic environments - Kunlin Chen; Lin Zhou; Jingyi Gu; Xiaolin Huang; Yaqi Zeng; Qingqi Wen; Jiale Yue; Chengshuai Liu; Weilin Huang; Qiaoyun Zeng; Chengyu Chen (Process Safety and Environmental Protection, 2026)

Density-dependent effects of net-chasing training on aggression, stress, and metabolic load in the freshwater prawn Macrobrachium rosenbergii - Jiangtao Li; Jiale Zhou; Zhongjie You; Zheng Xiao; Licheng Zeng; Li Lin; Xiaojing Lv (Aquaculture, 2026)

Metabolomics reveals GABA as a key mediator of salinity stress in razor clam - Geqi Gao; Zihan Lin; Yuting Han; Mengwei Shang; Jiahui Sun; Donghong Niu; Jiale Li (Aquaculture, 2026)

Phytochrome-interacting factors (PIFs): Integrating phytohormone signals at the nexus of development and stress adaptation - Jiale Yuan; Ruiyun Wang; Xifeng Ju; Fang Lin (Journal of Plant Physiology, 2026)

Surface piezotronics in centrosymmetric silicon for ultra-sensitive strain sensing and mechanoelectronic transduction - Mingqiang Zhong; Shaopeng Wang; Tianli Meng; Ao Li; Jiale Lv; Ehud Gazit; Zhong Lin Wang; Rusen Yang (Chemical Engineering Journal, 2026)

Acquisition and temporal transcriptomic characteristics of cambial meristematic cells in Camptotheca acuminata under in vitro culture conditions - Yundan Xiong; Shuang Yu; Jiale Sun; Zhiyu Chen; Fanfan Lin; Yifan Cai; Tianping Huang; Xin Yin; Yan Zheng; Yunqiang Yang; Xiangxiang Kong; Yongping Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Self-reporting and high-energy supercapacitors enabled by electrochromic ZnCo-S@CuFe-LDH heterostructures via interfacial engineering - Jiale Hou; Zhenghu Zhu; Haofeng Lu; Hecong Wang; Cheng Chen; Xinfeng Wu; Yonghou Xiao; Wanghui Wei; Minjie Xue; Lexing You; Xinzhou Ma; Donghai Lin (Chemical Engineering Journal, 2026)

Self-powered water quality optical inspection as mechanically triggered by time-controlled instantaneous discharging - Zixian Lai; Minyan Zhang; Guoliang Fu; Jiale Chen; Zhijian Li; Jiaqi Wang; Zhong Lin Wang (Chemical Engineering Journal, 2025)

A stacking ensemble learning approach for accurate and interpretable prediction of ship energy consumption - Liangkun Xu; Zhiheng Lin; Weihao Ma; Zhihui Hu; Liyan Cai; Jiale Li (Frontiers in Marine Science, 2025)
The accuracy and interpretability of ship energy consumption prediction results are important for ship energy efficiency optimization. In order to improve the accuracy of ship energy consumption prediction and enhance the model interpretability, this paper proposes a ship energy consumption prediction method based on Stacking and SHAP. Firstly, based on Stacking theory, multiple heterogeneous and complementary base models were selected using residual correlation analysis methods to construct a fusion model. And then, to address the “black box” characteristics of the fusion model, SHAP is used to analyze the base model and energy consumption impact characteristics of the fusion model in terms of their interpretability. A large container ship is used as the research object to verify the effectiveness and interpretability of the proposed method. The experimental results show that, in terms of accuracy, compared with the best single model (RF), the mean absolute error (MAE), mean square error (MSE), and root mean square error (RMSE) of the Stacking fusion model are reduced by 4.1%, 16.1%, and 8.3%, respectively, and the R² is improved by 1.5%. Meanwhile, in terms of interpretability, SHAP reveals that Random Forest (RF), k-Nearest Neighbor (KNN), and Gradient Boosting (GB) models play a dominant role in the fusion model, with a total contribution value of about 67%. In addition, sailing speed, mean draft, and trim are the main factors affecting the energy consumption of a ship, and the contribution value of each influential feature can be quantitatively measured. The proposed method ensures the prediction accuracy while enhancing the model interpretability, which can provide more reliable and transparent decision support for ship energy efficiency management.

Who you are versus where you are: Revealing the importance of determinants of within-city income inequality in China through an interpretable machine learning approach - Zuge Xing; Canfei He; Jiale Lin; Yuxin Pan (Applied Geography, 2025)

Carbon footprint of China's healthcare system from a global perspective: A multi-dimensional hotspot assessment - Han Zhao; Weiyi Liao; Lin Fu; Mengzhen Zhao; Shangchen Zhang; Jiale Wu; Peipei Chai; Wenjia Cai (Sustainable Production and Consumption, 2025)

Multi-omics approaches provide insights into adaptation to low salinity of intertidal clams - Zihan Lin; Honglei Wang; Geqi Gao; Hongtao Nie; Kai Ye; Donghong Niu; Jiale Li (Marine Environmental Research, 2025)

Enhanced volatile fatty acids production through anaerobic co-fermentation of dewatered sludge and food waste: Insights into performance, microbial dynamics and metabolic pathways - Wei Jiang; Yuanshou Jiang; Jiale Tao; Jiwu Luo; Wengang Xie; Xiaojuan Zhou; Lin Yang; Jianxiong Kang; Yuanyao Ye (Journal of Environmental Chemical Engineering, 2025)

Characterization of IL-34 and CSF-1R in Sciaenops ocellatus: IL-34 participates in its anti-bacterial immune responses to Vibrio harveyi infection - Jiale Zhou; Jingyao Yu; Lin Zhang; Qing Chu (Fish & Shellfish Immunology, 2025)

Environmental DNA reveals anthropogenic impacts on fish diversity in mountain streams and the increasing risk of species invasion - Yu Zhou; Yunchao Luo; Fan Yu; Zihong Zheng; Jidong Li; Yu Wang; Xu Wang; Jiale Cheng; Zhongqiu Li; Lin Wang; Aichun Xu (Anthropocene, 2025)

Antimicrobial properties and preservation potential of Allium sativum L-derived extracellular vesicle-like particles for food applications - Chenqi Zhu; Xiaoxiao Ke; Yi Gu; Chunmeng Wang; Shangyang Lin; Yijie Qian; Jiale Cheng; Yan Chen; Liu Xu; Zhipeng Chen (Food Chemistry, 2025)

Dual-functional tight ultrafiltration membrane constructed from aminoquinone networks for sufficient dye/salt selectivity and bacterial inactivation - Riri Liu; Hanna Vanermen; Jiale Du; Qin Chen; Zijian Yu; Junwei Li; Pengrui Jin; Junfeng Zheng; Alexander Volodin; Wenyuan Ye; Raf Dewil; Ming Xie; et al. (Desalination, 2025)

Optimal scheduling of industrial park integrated energy systems considering dynamics of multiple fluid networks - Yihui Mao; Xiaojie Lin; Shuting Zhang; Jiale Wang; Wei Zhong; Baoqin Liu; Guangyue Xia (Journal of Cleaner Production, 2025)

Graphite-catalyzed carbonization of biowaste unlocks energy-dense, high-rate, and long-lifespan potassium-ion batteries - Jiale Chen; Lulu Tan; Chengye Lin; Yue Bai; Xiaogang Niu; Zhe Zhang; Nan Li; Linlin Wang; Ye Wang; Xiao Ji; Yujie Zhu (Chemical Engineering Journal, 2025)

Evolution and influencing factors of regional economic inequality in China based on data from nighttime lights - Zuge Xing; Canfei He; Jiale Lin (Science China Earth Sciences, 2025)

Tight ultrafiltration membranes based on engineered metal-monophenolic networks for efficient dye/NaCl separation - Riri Liu; Qin Chen; Jiale Du; Yanyan Liu; Alexander Volodin; Patricia Luis; Wenyuan Ye; Raf Dewil; Ming Xie; Jiuyang Lin; Bart Van der Bruggen (Desalination, 2025)

Bimetallic MOF-derived Co/Ni@C and MXene co-decorated cellulose-derived carbon foams for absorption-dominated electromagnetic interference shielding - Fang Ren; Lin Ma; Chunjie Li; Tong Wu; Jiale Zhang; Lu Pei; Yanling Jin; Zhenfeng Sun; Zhengzheng Guo; Ping Song; Penggang Ren (Carbohydrate Polymers, 2025)

Ecotoxicological effects of the neonicotinoid insecticide dinotefuran on springtails (Folsomia candida) at soil residual concentration - Jiale Zhang; Herui Zhang; Caihong Yu; Ronghua Lin; Yanhua Hou; Min Li; Huixin Liang; Liping Chen; Xinyue Gao; Siqi Chen (Pesticide Biochemistry and Physiology, 2025)

Fine mapping of weight-QTL qBWE17 and cloning of candidate genes with functional analysis of growth-related haplotypes in black carp - Hao Lu; Jiamin Guo; Siyang Zhou; Lin Yang; Jiale Li; Yubang Shen (Aquaculture, 2025)

Genome-wide association study for growth traits in black carp (Mylopharyngodon piceus) - Siyang Zhou; Lin Yang; Jiale Li; Yubang Shen (Aquaculture, 2025)

Data-driven optimization of nose profiles for water entry impact load reduction - Kai Lv; Enfan Lin; Yongze Liu; Zongbao Chen; Yexian Wang; Ming He; Jiale Yan; Pengyu Lv; Yantao Yang; Hongyuan Li; Huiling Duan (Ocean Engineering, 2025)

Effects of light intensity and light duration on growth performance and ovarian development in red swamp crayfish Procambarus clarkii (Girard, 1852) - Long Wang; Meng Hu; Lin Cai; Yurui Wang; Tianyu Guan; Chuankun Zhu; Hui Wang; Guiling Wang; Jiale Li (Aquaculture International, 2025)

Derivation of ecological safety thresholds and risk assessment of new SDHI fungicides in farmland system - Jiale Zhang; Herui Zhang; Ronghua Lin; Yanhua Hou; Menglun Wang; Nan Zhang; Caihong Yu (Science of The Total Environment, 2024)

Thin-film composite electro-nanofiltration membrane for one-step and efficient fractionation of dyes and salts in high-salinity textile wastewater - Shuangling Xie; Zijian Yu; Lianxin Chen; Jiale Du; Jiangjing Li; Weishuang Yuan; Xiaojuan Li; Jiuyang Lin (Desalination, 2024)

The construction of a peptide vaccine with multifunctional DNA tetrahedron exoskeleton - Jiale Liang; Xin Qin; Siqi Xu; Mei Zhang; Lan Yao; Zhiqiang Liu; Geru Zhang; Taoran Tian; Yunfeng Lin (Chemical Engineering Journal, 2024)

Remote sensing inversion of suspended particulate matter in the estuary of the Pinglu Canal in China based on machine learning algorithms - Jinying Mo; Yichao Tian; Jiale Wang; Qiang Zhang; Yali Zhang; Jin Tao; Junliang Lin (Frontiers in Marine Science, 2024)
Introduction Suspended particulate matter (SPM) is a critical indicator of water quality and has a significant impact on the nearshore ecological environment. Consequently, the quantitative evaluation of SPM concentrations is essential for managing nearshore environments and planning marine resources. Methods This study utilized Sentinel-2’s single band and water index variables to develop a remote sensing inversion model for oceanic SPM in the estuary of the Pinglu Canal in China. Six machine learning algorithms were employed: K-nearest neighbor regression (KNNR), AdaBoost regression (ABR), random forest (RF), gradient boosting regression (GBR), extreme gradient boosting regression (XGBR), and light generalized boosted regression (LGBM). The model with the optimal performance was then selected for further analysis. This research applied the established model to investigate the spatial-temporal dynamics of SPM from 2021 to 2023. Results The findings indicated that (1) the XGBR algorithm exhibited superior performance (R 2 = 0.9042, RMSE = 3.0258 mg/L), with LGBM (R 2 =0.8258, RMSE = 4.0813 mg/L) and GBR (R 2 = 0.823, RMSE = 4.3477 mg/L) also demonstrating effective fitting. However, the ABR, RF, and KNNR algorithms produced less satisfactory fitting results. (2) Additionally, the study revealed that the combination of input variables in the XGBR algorithm was more accurate than single-variable inputs. (3) The contribution of single-band variables to the XGBR algorithm surpassed that of water index variables, with B12, B4, and B11 emerging as the top three influential variables in the model. (4) The annual SPM concentration in the study area exhibited an overall increasing trend, while its spatial distribution generally decreased from the estuary toward the Maowei Sea and Qinzhou Bay. Discussion The combination of Sentinel-2 data and XGBR model has shown good performance in retrieving SPM concentration, providing a new method and approach for large-scale estimation of SPM concentration.

Coordinated measurement of marine economy: High-quality and low-carbon development in China - Lin Pan; Qingwu Meng; Zhiwen Wang; Jiale Wu; Jing Yu (Ocean & Coastal Management, 2024)

Enhancement of methane production from anaerobic co-digestion of food waste and dewatered sludge by thermal, ultrasonic and alkaline technologies integrated with protease pretreatment - Wei Jiang; Yuanshou Jiang; Jiale Tao; Jiwu Luo; Wengang Xie; Xiaojuan Zhou; Lin Yang; Yuanyao Ye (Bioresource Technology, 2024)

Research on the wear resistance and impact resistance of modified rubberized concrete - Shucheng Yuan; Fengyu Zhang; SiWei Du; Kunpeng Li; Jiale Luo; Yuancong Liu; Zhanyuan Zhu; Jiangfeng Dong; Wei Liang; Jincheng Lin (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Zero-strain Co-doped Na2FeP2O7/carbon delivers superior rate capability and long-cycle stability for sodium ion batteries - Jianhong Gao; Ziwei Chen; Wei Cao; Jiale Chen; Ming Zhang; Feng Lin; Yongsheng Li; Waqar Ahmad; Min Ling; Chengdu Liang; Jun Chen (Chemical Engineering Journal, 2024)

High-performance antibacterial tight ultrafiltration membrane constructed by co-deposition of dopamine and tobramycin for sustainable high-salinity textile wastewater management - Wenyuan Ye; Fan Yu; Zijian Yu; Na Kong; Xiaoyan Lin; Riri Liu; Jiale Du; Xuan Huang; Ailiang Gu; Sotto Arcadio; Wenyi Zhang; Xuewei Li; et al. (Desalination, 2024)

Effects of microtopography on soil microbial communities in alpine meadows on the Qinghai-Tibetan Plateau - Xinwei Li; Xilai Li; Yan Shi; Shoujing Zhao; Jiale Liu; Yinyi Lin; Chunli Li; Chunhui Zhang (CATENA, 2024)

Effects of chronic abamectin stress on growth performance, digestive capacity, and defense systems in red swamp crayfish (Procambarus clarkii) - Tianyu Guan; Long Wang; Meng Hu; Qianqian Zhu; Lin Cai; Yurui Wang; Peng Xie; Jianbin Feng; Hui Wang; Jiale Li (Aquatic Toxicology, 2024)

A MXene heterostructure-based piezoionic sensor for wearable sensing applications - Lin Li; Jiale Pan; Longfei Chang; Zhihao Liu; Guan Wu; Ying Hu (Chemical Engineering Journal, 2024)

Interfacial Mo-S bond-reinforced hierarchical S-scheme heterostructure of Bi2MoO6@ZnIn2S4 for highly-selective and efficient CO2 photoreduction into CO - Jiale He; Jie Lin; Yu Zhang; Yingfei Hu; Qingling Huang; Guobing Zhou; Wei Li; Jianqiang Hu; Na Hu; Zhen Yang (Chemical Engineering Journal, 2024)

Anaerobic biodegradation of azo dye reactive black 5 by a novel strain Shewanella sp. SR1: Pathway and mechanisms - Jiale Liu; Lu Fan; Wenjun Yin; Shusheng Zhang; Xiaomei Su; Hongjun Lin; Haiying Yu; Zhenghai Jiang; Faqian Sun (Journal of Environmental Management, 2023)

Overcoming the fluorescent interference during Raman spectroscopy detection of microplastics - Yu Liu; Jiale Hu; Liqian Lin; Bing Yang; Minhua Huang; Min Chang; Xiaoxin Huang; Zhenqing Dai; Shengli Sun; Lei Ren; Chengyong Li (Science of The Total Environment, 2023)

Preparation, characterization, and evaluation of the antitumor effect of kaempferol nanosuspensions - Wen He; Junfeng Zhang; Jiale Ju; Yinghua Wu; Yuxi Zhang; Lin Zhan; Chenchen Li; Yanli Wang (Drug Delivery and Translational Research, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

Identification of Genes Related to Resistance to Ichthyophthirius multifiliis Based on Co-expression Network Analysis in Grass Carp - Feng Chen; Wei Zhang; Xiaoyan Xu; Lang Gui; Yanfeng Lin; Minglin Wu; Jiale Li; Yubang Shen (Marine Biotechnology, 2023)

A turn-on signal biosensor for cadmium(II) based on DNAzyme and stem-loop qPCR - Jiale Li; Zaihui Du; Pengfei Wang; Keren Chen; Shenghao Lin; Wentao Xu; Longjiao Zhu (Analytica Chimica Acta, 2023)

Effects of climate change on long-term building heating performance of medium-deep borehole heat exchanger coupled heat pump - Sheng Zhang; Jun Liu; Xia Zhang; Dun Niu; Fenghao Wang; Jiale Chai; Yalin Lu; Yongjun Sun; Zhang Lin (Energy and Buildings, 2023)

H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2023)

Quantitative study on steam system thermal inertia based on a dynamic hydraulic analytical model - Wei Zhong; Shuting Zhang; Xiaojie Lin; Jiale Wang; Yi Zhou (Journal of Cleaner Production, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

SATB1/SLC7A11/HO-1 Axis Ameliorates Ferroptosis in Neuron Cells After Ischemic Stroke by Danhong Injection - Sikai Zhan; Jiayin Liang; Huiting Lin; Jiale Cai; Xinxin Yang; Hongwei Wu; Junying Wei; Shumei Wang; Minghua Xian (Molecular Neurobiology, 2023)

The full-length genome sequence of a novel amalgavirus in Lilium spp. in China - Yanyan Huo; Xiaoting Li; Jiale Zhou; Shengjie Lin; Jiahao Ding; Huan Liu; Jianglian Yu; Ni Hong; Guoping Wang; Fang Ding (Archives of Virology, 2022)

Upregulated TRIM32 correlates with enhanced cell proliferation and poor prognosis in hepatocellular carcinoma - Xiaopeng Cui; Zhipeng Lin; Yuyan Chen; Xiaofei Mao; Wenkai Ni; Jinxia Liu; Huiling Zhou; Xiaohang Shan; Lingling Chen; Jiale Lv; Zhongyi Shen; Chengwei Duan; et al. (Molecular and Cellular Biochemistry, 2016)

Identification of housekeeping genes suitable for gene expression analysis in the pearl mussel, Hyriopsis cumingii, during biomineralization - Zhiyi Bai; Jingyun Lin; Keyi Ma; Guiling Wang; Donghong Niu; Jiale Li (Molecular Genetics and Genomics, 2014)

Lactosyl derivatives function in a rat model of severe burn shock by acting as antagonists against CD11b of integrin on leukocytes - Zhihui Zhao; Qing Li; Jiale Hu; Zhongjun Li; Jinghua Liu; Aihua Liu; Peng Deng; Lin Zhang; Xiaowei Gong; Kesen Zhao; Shuangquan Zhang; Yong Jiang (Glycoconjugate Journal, 2009)